Plant productivity and microbial composition drive soil carbon and nitrogen sequestrations following cropland abandonment - Li, Jiwei; Li, Miaoyu; Dong, Lingbo; Wang, Kaibo; Liu, Yulin; Hai, Xuying; Pan, Yingjie; Lv, Wenwen; Wang, Xiaozhen; Shangguan, Zhouping; Deng, Lei (The Science of the total environment, 2020)
Understanding the variations in soil organic carbon (SOC) and total nitrogen (STN) stocks in the different ages of abandoned cropland ecosystems of different ages is essential for land use decisions to maximize C sinks or improve ecosystem services. However, knowledge of the dynamics of SOC and STN stocks and their controlling factors after cropland abandonment is limited. Thus, this study investigated the changes in the SOC and STN stocks of loessal soil (Calcaric Regosols) with a chronosequence of 3, 8, 13, 18, 23 and 30 years following cropland abandonment on the Loess Plateau. As a whole, we examined 42 field plots and implemented multivariable linear regression analysis (MLRA) and structural equation modeling (SEM) using 22 influencing variables related to plant, soil and microbial properties to quantify the controls of SOC and STN stocks. The results revealed that SOC and STN stocks significantly increased after cropland abandonment for 30 years, and there were minor decreases in C and N sequestrations in the early restoration stage (<18 years). The SOC and STN changes had significant positive correlations, in which that exhibited STN stocks shifted concurrently with the rate of relative SOC stock changes. The MLRA models demonstrated that the SOC stocks were primarily controlled by aboveground biomass, STN, fungi, and the ratio of fungi to bacteria, while STN stocks were mainly driven by root biomass, above-ground biomass, STN, fungi and the ratio of fungi to bacteria after cropland abandonment. The SEM models further demonstrated that plant productivity not only directly determined the variations in SOC and STN stocks but also changed the microbial community following post-cropland restoration. These results suggest that long-term (>18 years) cropland abandonment can be a successful approach for reinstating SOC and STN stocks, while plants and microbes together mediate microbial C and N stocks during vegetation succession in a semiarid region. [Display omitted] •Minor decreases in soil C and N accumulations of early stage after cropland abandonment•Soil C and N accumulations are synchronous following postcropland abandonment.•Plant productivity and microbial composition determined the changes in soil C and N stocks.•Quantified the relative contributions of restoration age, plant, soil and microbe on soil C and N sequestrations.